Chaotic Genetic Enhancements to the Modified PlayFair Algorithm - Seth, Archi; Sankar Biswas, Siddhartha (International Journal of Computer Sciences and Engineering, 2025)
The central tenets of modern cryptography are data confidentiality, data integrity, authentication, and non-repudiation. There are a number of algorithms being used for confidential transmission of messages from one end to the other. The PlayFair Cipher is a substitution cipher. The classic PlayFair cipher uses 5 * 5 matrix to encrypt pairs of letters (diagrams).The frequency analysis is harder than simple substitution ciphers as there are 25 * 25 = 625 diagrams. But with increase in computing power, classical ciphers have become easy to break. The classical substitution ciphers can be broken by cipher text-only attacks. This paper presents a modified version of the classical PlayFair Cipher. The improvement is done to the original 5 * 5 cipher to modify it to 10 * 9 matrix. The matrix uses uppercase and lowercase English characters, numbers, punctuation marks and some special characters. The security aspect is enhanced by the use of Chaotic Genetic Algorithm to encrypt the cipher text again using Genetic crossover and mutation operations with a Chaotic Pseudo Random Sequence.